Electrohydrodynamic Model Of Electron Microscope - Mačák, Martin (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
This work presents a complex multiphysics model of an electron microscope in ANSYSFluent software. A custom electromagnetic model was used to describe the relativistic transport ofelectrons. The model consisted of a description of an electromagnetic field, relativistic transport ofcharged particles and interactions between charged particles and solid materials. Presented resultssuggest, that the custom model can be coupled with the CFD module, which results in a possibilityof coupled simultaneous simulations of hydrodynamics, electromagnetics, and a transport of chargedparticles.
Keywords: Electron microscope; numerical modelling; ANSYS Fluent; relativistic transport